(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The present article aims to contextualize and discuss contributions around the investigations and research on Afro-diasporic dances in urban contexts for Dance education, seeking to understand their characteristics, intersections, and challenges in order to expand and complexify processes related to ways of teaching-learning dances. To this end, the text highlights some Afro-diasporic dances, their characteristics, and aesthetic traits reminiscent of the African continent, as well as proposes to reflect on the specificities of Afro-diasporic knowledge-practices that allow us to understand their contributions to education in the context of a higher education course in Dance.